Analisis Studi Kelayakan Bisnis pada UMKM : Studi pada Rezzen Bakery - Asari, Fahreza Naafi; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2025)
Rezzen Bakery is one of the pioneers of the coffee and bakery concept in Malang. The business has evolved from a home-based venture to a more professional establishment with better facilities and supported by local labor. This business feasibility study was conducted to evaluate the legal, environmental, marketing, technical and technological, management and human resources (HR), financial aspects, and environmental impact analysis (Amdal). Through observations and interviews, this study aims to assess the feasibility of the business and identify the most efficient strategies for future development. The analysis results show that Rezzen Bakery performs "good" to "very good" in various aspects, with key strengths in legality, environmental management, technology, and HR management. However, some areas, such as financial operational efficiency and social impact, still require improvement to support the business’s sustainability. Overall, the business is deemed feasible and has great potential for further growth with the implementation of optimal strategies.